COMPARATIVE STUDY OF CUCURBITACEAE MEDICINAL PLANTS FOR PHYSICOCHEMICAL PARAMETERS - Shivhare, Yogesh; Jain, Alok Pal (Journal of Biomedical and Pharmaceutical Research, 2019)
Modern research tool for evaluation of plant drugs are available today but physicochemical method is the one simplest and reasonable method for the assessment of quality and purity of crude plant materials. With the aim of drawing the physicochemical parameters of Cucurbitaceae family, the present study deals with leaves of all the selected Coccinia indica, Momordica dioica, Praecitrullus fistulosus, Trichosanthes dioica medicinal plants. The Obtained information will be used for further help in identifying the crude drug as potent therapeutic agents and assist in standardization for excellence and clarity. Keywords: Physicochemical, Ash, Cucurbitaceae, Leaves